Association Between Serum Vitamin D Levels and Acute Respiratory Tract Infections Among Preschool Children in Gharyan Hospital, Libya - Najah Rajab Ghoumah; Mustafa Saieh (African Journal of Advanced Pure and Applied Sciences, 2026)
Background: Acute respiratory tract infections (ARTIs) remain one of the leading causes of morbidity and hospitalization among preschool children worldwide. particularly in low- and middle- income countries. Vitamin D plays a crucial immunomodulatory role in respiratory health by enhancing innate immunity and maintaining epithelial barrier integrity. However, vitamin D deficiency is highly prevalent among children, including those living in sun- rich regions such as Libya. Objectives: This study aimed to assess serum vitamin D levels among preschool children admitted with ARTIs at Gharyan Central Teaching Hospital and to evaluate the association between vitamin D status, disease severity, and recurrence. Methods: A cross-sectional observation study was conducted among 100 preschool children aged 1-6 years admitted with clinically diagnosed ARTIs between January and December 2025. After applying the inclusion and exclusion criteria, 79 eligible participants were included in the final analysis. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured and categorized according to Endocrine Society guidelines. Associations between vitamin D levels, ARTIs severity, and recurrence were analysed using chi-square tests and logistic regression models. Results: Vitamin D deficiency and insufficiency were highly prevalent, affecting 87.3% of the studied children. Although lower vitamin D levels were more frequently observed among children with moderate and severe ARTIs, the association with disease severity was not statistically significant (p=0.115). In contrast, a significant association was identified between low vitamin D levels and recurrent ARTIs (p=0.019). Conclusion: Vitamin D deficiency is highly prevalent among preschool children hospitalized with ARTIs and is significantly associated with recurrent infections. Improving vitamin D status may contribute to reducing the recurrence of ARTIs in this population.